CREATION OF CREATIVE PROJECTS BY THE MEANS OF ICT AS THE CONDITION OF EFFECTIVE FORMATION OF QUASI PROFESSIONAL EXPERIENCE OF THE FUTURE MUSIC PEDAGOGUE - Synevych, І. С. (Journal of Information Technologies in Education (ITE), 2018)
The article is considering a quasi-professional activity and its impact on the formation of future specialist musicians’ professional and pedagogical orientation; is describing students’ practical-oriented theoretical training in the process of quasi-professional experience formation. The role of innovation technology, i.e. designing in formation of quasi-professional experience is defined. Essence, features, and requirements for the project activity are solved. Different student musicians’ kinds of projects, structure and stages of creative projects’ preparation are analyzed. Considerable attention is paid to the analysis of the use of ICT, in particular multimedia in work on creative projects that favors formation of quasi-professional experience, information competence, develops students’ computer literacy. Microsoft PowerPoint that is a part of Microsoft Office is the most suitable multimedia tool that gives opportunities to present the results of the future specialist musician’s project activity. The article deals with the information of an effective work with the program, the structure of presentation which ensures the preservation of the information’s integrity, stages and principles of development, rules of using are defined. It is theoretically proved that the use of multimedia presentations and creative project activity promotes the increasing of students activity and the effectiveness of the educational process, realizes the potential of independent research and research activity and the future teachers’-musician creativity, promotes formation of quasi-professional experience of future specialists.